Examining the Impact of Immediate Family Members on Gulf Arab EFL Students' Strategic Language Learning and Development. (August 2019) - Hajar, Anas
This article provides a qualitative inquiry into the influences of immediate family members (i.e. parents and siblings) on a group of Gulf Arab EFL students regarding their language learning experiences and strategy use in their Arab homelands. The participants came from financially comfortable families, with different levels of education. The data collected from a written narrative and four subsequent semi-structured interviews suggest that the occupation and educational attainment of the participants' family figures (mostly parents) affected the amount and kind of support these families offered to the participants while learning English. Less educated parents involved themselves indirectly in their children's English language learning, and their involvement appeared at a late stage in the participants' academic lives in the form of emotional and/or financial support. The language learning strategies (LLSs) used by these participants were mainly exam-oriented. Conversely, higher educated parents contributed to enabling their children to enact their desired future self-images confidently as English speakers from the beginning, for example by sending them to well-resourced private educational establishments throughout their education. From this qualitative study, pedagogical implications as well as areas for ongoing research are suggested.